Proceedings of the 1st Economics and Business International Conference 2017 (EBIC 2017) 2018
DOI: 10.2991/ebic-17.2018.90
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Entrepreneurial Marketing on Competitive Advantage: Small Culinary Souvenir Industry in Jalan Mojopahit Medan, Indonesia

Abstract: This study aims to investigate the effect of entrepreneurial marketing dimensions namely: pro-activeness; calculated risk-taking; innovativeness; opportunity focus; resource leveraging; customer intensity and value creation on competitive advantage in small Medan culinary souvenir industry in Jalan Mojopahit Medan, Indonesia. This study uses thirty-four samples. Data analysis used in this study is multiple linear regression. This multiple regression analysis indicates that entrepreneurial marketing has signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Research has been carried out into the relationship between EM and outcome goals such as business growth (Janet and Ngugi, 2014;Maziriri et al, 2018), customer and financial success (Becherer et al, 2012), competitive advantage (Khouroh et al, 2020;Makmur et al, 2018), innovative performance (Hacioglu et al, 2012) and business performance (BP) (Adel et al, 2020). In particular, the relationship between EM and BP has been extensively analyzed over the past few years (Fard and Amiri, 2018;Mugambi and Karugu, 2017;Rezvani and Fathollahzadeh, 2020;Sadiku-Dushi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research has been carried out into the relationship between EM and outcome goals such as business growth (Janet and Ngugi, 2014;Maziriri et al, 2018), customer and financial success (Becherer et al, 2012), competitive advantage (Khouroh et al, 2020;Makmur et al, 2018), innovative performance (Hacioglu et al, 2012) and business performance (BP) (Adel et al, 2020). In particular, the relationship between EM and BP has been extensively analyzed over the past few years (Fard and Amiri, 2018;Mugambi and Karugu, 2017;Rezvani and Fathollahzadeh, 2020;Sadiku-Dushi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To identify gaps, researchers focused on entrepreneurial marketing research that is correlated with competitive advantage and firm performance. In this case, there is a pattern that emerges, namely that previous studies that used the same construct, gave different results (Makmur et al 2018 ; Sadiku-dushi et al 2019 ; Stephen et al 2019 ). Multidimensional entrepreneurial marketing constructs that contain dimensions of proactivity, calculated risk-taking, innovation, focus on opportunities, resource lifting, consumer intensity, and value creation have different effects on company performance.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Multidimensional entrepreneurial marketing constructs that contain dimensions of proactivity, calculated risk-taking, innovation, focus on opportunities, resource lifting, consumer intensity, and value creation have different effects on company performance. The study of Stephen et al ( 2019 ) found that competitive advantage is only significantly influenced by the dimensions of opportunity focus, innovation, resource leveraging, and value creation; meanwhile, Makmur et al ( 2018 ), in the local context, found different results where only the dimension of opportunity focuses proactivity, and resource lifting which have a significant effect on competitive advantage. This shows that the construct is still not sufficient to conceptualize entrepreneurial marketing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studi empiris yang menyelidiki dampak jejaring sosial dan ikatan lainnya pada kinerja ekonomi di Indonesia dilakukan oleh misalnya, Day & Rahman, 2011;Makmur et al, 2018;Dirgiatmo et al, 2019;Pudyastuti, 2020 Pada Gambar 1 menyiratkan ide bahwa untuk menciptakan dan memberikan nilai pelanggan yang unggul, entrepreneurial marketer harus mengetahui informasi pasar yang relevan, kebutuhan pelanggan saat ini, dan calon pelanggan, sehingga dapat dikatakan hal ini menjadi relevan karena pada pasar yang memang kompetitif, pembeli memiliki alternatif lain yang tersedia seperti di dalam pasar Indonesia. Pada UKM diharapkan entrepreneur akan menggunakan cara-cara kreatif untuk mendapatkan informasi pasar karena usaha mengembangkan pengetahuan mengenai pasar bisa jadi membutuhkan biaya yang cukup besar.…”
Section: Jejaring Sosial Dan Hubungan DIunclassified